2020
DOI: 10.3390/pr8080902
|View full text |Cite
|
Sign up to set email alerts
|

Potential Cultivation of Lactobacillus pentosus from Human Breastmilk with Rapid Monitoring through the Spectrophotometer Method

Abstract: The present study focused on the development of a new method to determine the lag phase of Lactobacillus in breast milk which was attained during the 1st, 3rd, and 6th month (M1, M3, and M6). The colonies’ phylogenetic analysis, derived from the 16S rRNA gene sequences, was evaluated with genus Lactobacillus pentosus and achieved a similarity value of 99%. Raman spectroscopy in optical densities of 600 nm (OD600) were used for six consecutive days to observe the changes of the cell growth rate. The values of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…The incubation was carried out for 72 h on a shaker at room temperature. Optical density (OD) values were analyzed every 24 h using a 600nm wavelength spectrophotometer (Nguyen-Sy et al, 2020). The OD value was used to determine cell density to observe the growth of Lactobacillus sp.…”
Section: Production Of Bioflavor In Substituted Mediummentioning
confidence: 99%
“…The incubation was carried out for 72 h on a shaker at room temperature. Optical density (OD) values were analyzed every 24 h using a 600nm wavelength spectrophotometer (Nguyen-Sy et al, 2020). The OD value was used to determine cell density to observe the growth of Lactobacillus sp.…”
Section: Production Of Bioflavor In Substituted Mediummentioning
confidence: 99%
“…In another cuvette, 1 mL of inoculum broth was loaded (Sample). The spectrophotometer's wavelength was set to 600nm, (32) and readings were recorded for the blank and sample cuvettes. The inoculum broth was diluted with TSB (with 5% sucrose) until the culture density reached 0.1.…”
Section: Bacterial Systemmentioning
confidence: 99%
“…bulgaricus and Lactobacillus acidophilus were above the recommended minimum number (≥ 10 6 cfu/g) 17 . Lactobacillus bacteria are considered to be organisms with high antimicrobial and probiotic potential 20 . Păucean et al showed that the addition of acacia honey in kefir production at 1%, 2.5%, and 4% (w/v) had no effect on the growth and viability of Lactococcus bacteria.…”
Section: Introductionmentioning
confidence: 99%